Tri-band cross-coupling bandpass filter with rectangular defected ground structure array. Issue 11 (24th July 2018) - Ma, M.-M.; Tang, Z.-X.; Cao, X.; Qian, T.
Abstract: A tri-band cross-coupling bandpass filter (BPF) with rectangular defected ground structure (DGS) array is proposed in this paper. Cross-coupling paths comprised of five resonators are employed to achieve general Chebyshev filtering frequency responses. Besides changing gaps among resonators, a novel rectangular DGS array is proposed to exactly meet coupling coefficients for specific demands for different passband in multi-band BPF. The centre frequency of the tri-band filter that is selected at 2.4, 3.4, 5.5 GHz are for LTE, Bluetooth, WiMAX and WLAN. The 3 dB bandwidth of the three passbands are 5, 3.23 and 3.45%, respectively, meanwhile, more transmission zeros are generated, leading to enhanced selectivity and high out of band isolation. The proposed tri-band filter is completed with a few simple calculations and several brief processes. Measured results of the fabricated filter demonstrate the theory prediction and proposed method well.